Solução de comunicação de baixo custo utilizando LoRa e ESP32 - Dias, Rodrigo Nunes (Universidade Federal de São Carlos, 2023)
This work deals with the evaluation of the average range of a local communication network with the LoRa protocol based on low-cost generic hardware and the establishment of its possible applications. A secondary objective would be to map the university campus of São Carlos of UFSCar for the future use of the proposed solution in application areas.
Low communication solution cost using LoRa and ESP32
Keywords: IoT; LoRa; Rede local; Local network; Médio alcance; Medium range; Baixo custo; Low cost; Internet das coisas; Internet of things; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::SISTEMAS DE COMPUTACAO